Trophic status of Pinang Luar Lake Buluhcina Village Siak Hulu District Kampar Regency Riau Province based on chlorophyll-a and phytoplankton - Ranee sly Panggabean; Asmika Harnalin Simarmata; Rina D’rita Sibagariang (Universitas Djuanda, 2026)
Chlorophyll a and phytoplankton are parameters that can be used to determine the trophic status of a body of water. The purpose of this study was to determine the trophic status of Lake Pinang Luar waters. The study was conducted from July to August 2024 in Lake Pinang Luar. Sampling was conducted at 3 stations: Station 1, Station 2, and Station 3of Lake Pinang Luar. At each station, there were 2 air sampling points: the surface and at a depth of 2 seconds (2 times the Secchi disk transparency). Sampling was carried out 6 times at 1-week intervals. The air quality parameters measured were chlorophyll a, phytoplankton, temperature, brightness, acidity (pH), free carbon dioxide (CO2), nitrate (NO3-), phosphate (PO43-), and dissolved oxygen (O2). The results of the study showed that the chlorophyll a concentration obtained was 10.16-13.98 µg/L, and the total reported phytoplankton was 4,884-11,704 cells/L. The air quality parameters measured during the study were temperature with a range of 29.2-30.3 °C, brightness 70.8-75.2 cm, acidity degree (pH) 5-5.2, free carbon dioxide (CO2) 3.76-12.30 mg/L, nitrate (NO3-) 0.12-0.34 mg/L, phosphate (PO43-) 0.08-0.14 mg/L and dissolved oxygen (O2) 3.58-6.11 mg/L. The trophic status of the waters of Lake Pinang Luar, based on chlorophyll a and phytoplankton, is moderate (mesotrophic). The supporting air quality parameters still support aquatic life, especially phytoplankton.